Functionings of Land Analysing Compulsory Acquisition Cases from Scotland - Rao, Jyoti (Springer Singapore, 2018)
This book focuses on the 'functionings' and capabilities generated from land by their owners and the challenge in satisfactorily recreating these through the compensation paid in the case of compulsory acquisition of private land. These discussions initiate a new debate on the insufficiency of existing approaches to compensation that are ignorant of the losses of 'capabilities' and 'functionings'. The relationship between land, ownership and well-being of an individual is explained through the identification of various 'functionings' associated with the ownership of land in the context of Scotland. Contemporary approaches to compensation, founded on the utilitarian argument, have led to dissatisfactory outcomes for the affected landowners. Discussions in this book shift the focus to equalizing the share of burdens and benefits for each individual member of the society, through equalization of human capabilities. This book will be of value to development economists, researchers, policy makers and law makers concerned with compulsory acquisition of land. Jyoti Rao is an early career researcher pursuing doctoral research at the University of Melbourne. Her primary research interest is in issues related to housing, urban development, and land economics with most of her publications being in related fields. Jyoti is a trained architect, urban planner and real estate professional with experience of working in the industry and in academia.